Implementing the 1993 Nunavut Land Claims Agreement - Campbell, Alastair; Fenge, Terry; Hanson, Udloriak (Arctic Review on Law and Politics, 2011)
Following more than 20 years of research and negotiation, the Nunavut Land Claims Agreement (NLCA) was ratified by Inuit and the Government of Canada in 1993. The territory of Nunavut and the Government of Nunavut were established in 1999 pursuant to the Agreement. In exchange for a wide range of constitutionally protected rights and benefits, the Inuit of Nunavut ceded to the Crown «all their aboriginal claims, rights, titles and interests . to lands and waters anywhere within Canada .» While much has been accomplished through the Agreement, huge implementation challenges remain. Successful implementation of the Agreement requires a firm and enduring partnership between the Inuit of Nunavut and the governments of Canada and Nunavut. To ensure that this partnership is effective and to safeguard the «honour of the Crown,» the Government of Canada should adopt policies and inter-agency and inter-governmental processes to ensure the Agreement is fully implemented.Keywords: Inuit, Nunavut Agreement, Implementation, Government of Canada, LitigationCitation: Arctic Review on Law and Politics, vol. 2, 1/2011 p. 25–51. ISSN 1891-6252